Metode Prototipe Aplikasi Klasifikasi Pengaduan Masyarakat Menggunakan Algorithma Naive Bayes Berbasis Website - Muhammad Aidil Adham; Ryci Rahmatil Fiska; Muhammad Asep Subandri (Politeknik Kampar, 2024)
Information technology plays a crucial role in improving public services, particularly in handling citizen complaints. Citizens often face obstacles in reporting complaints due to complex bureaucracy and limited access. To address these issues, this study aims to develop a web-based citizen complaint classification application using the Naïve Bayes algorithm. The application is designed to automatically classify complaints and direct them to the appropriate agencies, such as the Fire Department (DAMKAR), Public Works Department (DPU), and Regional Drinking Water Company (PDAM). The Naïve Bayes algorithm is utilized for its ability to calculate probabilities and produce accurate classifications. The application was developed using the prototype method, which allows for iterative processes and adjustments based on user feedback. System testing demonstrates that this application functions well and meets the needs of relevant agencies in efficiently handling public complaints.